Clinical risk factors for the development of hypertension in patients treated with inhibitors of the VEGF signaling pathway - Hamnvik, Ole-Petter R. (Cancer, 2014)
BACKGROUND: VEGF signaling pathway inhibitor (anti-VEGF) therapy is associated with hypertension, but little is known about predisposing clinical characteristics. This study describes the real-world association between baseline clinical characteristics, blood pressure (BP) response, and survival in patients prescribed anti-VEGF therapies. METHODS: Clinical data from Partners HealthCare in Massachusetts was obtained from adults treated with anti-VEGF therapies (2002–2013). Treatment-induced hypertensive response was defined as worsening of pre-existing hypertension or new diagnosis of hypertension (if no prior hypertension history). RESULTS: Data from 1120 patients with renal cell carcinoma (32.2%), hepatocellular carcinoma (11.6%), gastrointestinal stromal tumors (12.5%) and other sarcomas (15.3%) were analyzed. Most patients received sunitinib (52%), sorafenib (25.9%) or pazopanib (18%). A treatment-induced hypertensive response was identified in 49.7% of treated patients. Pre-existing hypertension, present in 65.4%, was an independent risk factor for BP elevation (odds ratio (OR) 1.56, 95% confidence interval (CI) 1.27–1.92); other risk factors included age ≥60 years (OR 1.26, 95%CI 1.06–1.52), and body mass index (BMI) ≥25 kg/m(2) (OR 1.26, 95%CI 1.04–1.53). Race, gender, anti-VEGF therapy prescribed, and baseline antihypertensive class were not significant risk factors. The absolute observed mean increase in BP was 21 mmHg (systolic) / 15 mmHg (diastolic), both in patients with and without pre-existing hypertension. The development of hypertension predicted improved survival (hazard ratio 0.76, 95%CI 0.65–0.89). CONCLUSIONS: Pre-existing hypertension, age, and BMI identify patients at risk for significant anti-VEGF therapy-induced BP elevation. Hypertension appears to be a clinical biomarker of efficacy to anti-VEGF therapies in a broad range of malignancies.